Implementasi Pembelajaran Tajwid Menggunakan Buku Panduan Bahan Ajar (PBA) Untuk Meningkatkan Kemampuan Membaca Al-qur’an di Rumah Qur’an Bunda Aisyah 17 lampung - Loviana, Shelvia; Nugroho, Anggi Septia; Basyar, Muslim (Widya Balina, 2023)
The Qur'an is the word of Allah which was revealed to the Prophet Muhammad SAW, through the intermediary of the Angel Gabriel (AS). This research discusses the implementation of recitation learning using the Teaching Material Guide (PBA) book to improve the ability to read the Qur'an at Mother Aisyah's Qur'an House. This research aims to find out how to implement recitation learning using the Teaching Material Guide (PBA). This study uses a qualitative method. Data collection techniques are observation, interviews and documentation. Based on the data analysis that has been carried out, it can be concluded that the Qur'an House is an Al Qur'an Education institution. Teaching and learning activities are carried out twice a week using the Teaching Material Guide (PBA) book. Tholibah's ability to read the Qur'an is categorized as good. The implementation of recitation learning using the Teaching Material Guide (PBA) book has 3 stages, namely the opening stage, the core stage and the closing stage. As for the imtihan or exam as an evaluation, the results of the exam can see which tholibah have met the target and which have not.